Sound absorption and transmission loss characteristics of 3D printed bio-degradable material with graded spherical perforations. (15th January 2022) - Sailesh, R.; Yuvaraj, L.; Doddamani, Mrityunjay; Babu Mailan Chinnapandi, Lenin; Pitchaimani, Jeyaraj
Highlights: Bio-degradable, functionally graded and uniform specimens with spherical perforations wereobtained by Fused Filament Fabrication based 3D printing. The graded perforations had a significant effect on the sound absorption and transmission loss characteristics. Functionally graded perforations registered better sound absorption characteristics in the low frequency region below 1000 Hz. Specimens with uniform bubbles in series showed better sound absorption for less size spherical porosity within the higher frequency range above 1000 Hz, Sound transmission loss characteristics of functionally graded specimens were better compared to all uniform bubble specimens and the margin increased with frequency. Abstract: The influence of spherical bubble perforations and their grading on acoustic characteristics of a 3D printed bio-degradable material is investigated. Samples with spherical bubble perforations of different sizes are distributed either uniformly or graded across the specimen thickness. A sample having typical cylindrical perforations is also analyzed for comparative analysis. Sound absorption (SA) and sound transmission loss (STL) characteristics are estimated by the impedance tube method. The results reveal that the SA of all functionally graded (FG) perforations is higher at low frequencies. The SA and bandwidth are higher for a specimen with uniform, lower diameter bubbles at higher frequencies. The STL of FG perforations is highest among the specimens, and the difference increases significantly with frequency. The numerical and experimental results match a high degree of accuracy. FG perforations exhibited superior performance for both SA and STL. The proposed graded spherical porosity can be effectively utilized in soundproofing applications across building and transportation sectors.